GATED MIBI MYOCARDIAL SPECT SHOWING BALANCED ISCHEMIA AND GLOBAL HYPOKINESIA IN PATIENT HAVING THROMBUS IN BASAL SEGMENT OF DOMINANT CIRCUMFLEX SYSTEM BLOCKING BOTH LEFT ANTERIOR DESCENDING AND CIRCUMFLEX ARTERY - Jielani, Asif; Khan, Amjad Aziz; Fatima, Tatheer; Ahmad, Shakil; Khan, Kamran; Zia, Nadeem; Zahaur, Zainab (Journal of Ayub Medical College Abbottabad, 2010)
Myocardial perfusion imaging (MPI) is a powerful diagnostic and prognostic tool for evaluating coronary artery disease (CAD). Gating myocardial perfusion gives important diagnostic and prognostic information. This 43 years old patient was referred for cardiac scan. Exercise stress test showed > 2mm horizontal ST segment depression. Cardiac scan was normal except for left ventricular cavity dilatation on stress images. Gated images showed global hypokinesia and increased end-diastolic volume. Patient was suspected to have balanced ischemia and was referred for Angiography. Angiography showed total occlusion with no flow in proximal Left Anterior Descending Artery and distal circumflex artery. It is very important to evaluate symptomatic patients and patients with risk factors carefully with normal myocardial perfusion scan.